The role of the regulator in SMS - Terry Kelly (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
In almost all cases, the transport industry has adopted safety management systems (SMS) in response to a regulatory initiative. SMS vary dramatically across transport modes and jurisdictions - often because of the influence of different legacy regulatory programmes, and the attendant cultures. Consequently, there is no single path to guarantee a regulatory authority success in designing and implementing SMS regulations. For many, SMS has become a voyage of discovery, an experiment in proactive safety management that is being conducted in real time. SMS has been a "step change" that has challenged industries in all modes of transport. It has severely taxed the capabilities of many regulatory authorities. It is arguably the most significant regulatory change that has occurred in the transportation industry in recent times. Regulating SMS has often led to revised legislation, regulations or standards; whole scale restructuring of the regulatory agency; new or revised regulatory protocols, processes, activities, and tools; and new information technology (IT) and new processes for information management (IM). SMS will continue to evolve in the coming decades. The paper draws on lessons learned to explore strategies that can be used to design, implement and operate the related regulatory programmes. Observations are provided to help decision makers manage the challenges they will predictably face. The critical role of dynamic, wide-reaching communications and strategic planning, with industry and within the regulatory organisation, is underlined.
Keywords: 330; Schienenverkehr; Verkehrssicherheit; Arbeitsschutz; Verkehrsrecht; Risikomanagement; Unternehmenskultur; OECD-Staaten-seitig